Questioning Devotions, Reorienting Commitments: Using Christian Religious Archives and Church History to Study Indian Residential Schools - Gaudet, Colby (Arc, 2023)
This paper is a methodological reflection on my time as a graduate student studying Indian Residential Schools through archival sources. I broadly survey relevant secondary studies to access the current state of the field and to chart prospective avenues for future scholarly engagement. I suggest that, for religionists, the frameworks of church history and mission history can be selectively utilized to examine the history of residential schooling. I argue that the ‘Indian Residential School’ (or IRS) terminology creates a narrowed understanding of colonialism and assimilative education by disregarding other modes of schooling deployed in Indigenous communities: the day schools and mission schools, but also hospitals, convents, and other church-operated institutions. Largely dating to the pre-Confederation period, mission schools especially fade from view when studies focus on the national model of the IRS launched in 1879 and expanded in 1884. In many regional contexts, mission schools of the colonial era laid the literal and conceptual groundwork for the later launching of the IRS system.By studying the works and the records of specific church bodies, religionists might elucidate with greater clarity the evolving differences, synchronicities, or collaborations of ideologies, policies, and practices among members of church and state over several centuries. Attending to pre-Confederation, colonial history also lends a transnational scope to a topic that is often framed in the context of national history, i.e., ‘Canada’s residential school system’. A global perspective on colonial education could assist historians of religion to assess the legacies of church, empire, and imperialism on Canada’s national model of residential schooling.